The incidence of significant relationships between selected parameters of feet and parameters of trunk in children aged 4, 5 and 6 years - Mrozkowiak, Mirosław; Sokołowski, Marek; Kaiser, Alicja; Posłuszny, Mariusz (Journal of Education, Health and Sport, 2018)
Introduction. The evolution of information technology has resulted in development of normative ranges with regard to the parameters of human body posture which led to further research of their mutual impact, relationships and concomitance. Material and method. The study conducted with the group of children aged 4 to 6 years enabled to record 2,988 observations with regard to the measurement of the 90 parameters describing trunk and feet. The station for an assessment of body posture and feet using the photogrammetric method consisted of a computer, a card, software, a display monitor, a printer and a projection-reception device with a camera to measure selected parameters. Findings 1. The values of left foot parameters correlated significantly more with trunk parameters than right foot parameters. Particularly high correlations were observed in the following parameters: length of the fifth arch, surface of plantokonturogram (the plantar side of the feet) and height of the fifth arch, valgity angle of the fifth toe, and heel angle of left foot. 2. Foot parameters revealed the most frequent significant relationship with trunk parameters in the sagittal and frontal planes. Trunk parameters with which foot parameters correlated most often included: asymmetry in the height of both scapulas with the right scapula up, inclination of thoracolumbar region and asymmetry in the height of waist triangles with the right triangle up.